Arabic borrowing of the Hebrew word menahēl ‘manager’: Articulations and ideologies - Hawker, N (John Benjamins Publishing, 2018)
Ideologies, or ways of understanding one’s relation to the world, impede or encourage, and affect the form of, language contact practices such as borrowing and codeswitching. This is illustrated by the pragmatic functions – informative or humorous – of the Israeli Hebrew word menahēl ‘boss’ in Palestinian Arabic. By using ‘boss’ in an ironic sense, to refer to a self-important ‘big-head’, Palestinians are expressing their stance by means of a Hebrew loanword, to take a dig at the powers that be. The article provides examples of real usage and grounds the explanation for the different meanings in pragmatics, cultural theory, and Althusser’s conception of ideologies in ways that are useful to linguistic ethnography.